Studies of Optimal Salinity of Nonionic Microemulsions - Kumar, Anil (Asian Journal of Chemistry, 2011)
The optimal salinity of non-ionic microemulsions containing Triton X-100+ 1-hexanol (1:5 molar ratios)/dodecane/water was studied in presence of different types of electrolytes at various temperatures. The volume measurement with increasing salinity reveals three types of Winsor formation (Winsor I, II and III). The optimal salinity determined by plotting solubilization parameters of oil, Vo/Vm and that of water, Vw/Vm against electrolyte concentration decreases with increase in temperature in presence of strong electrolyte. However, it does not change much with increase in temperature in presence of weak electrolyte. At constant temperature optimal salinity was found higher in presence of weak electrolyte as compared to strong electrolyte.